Respuesta :

Answer:

[tex]y=\dfrac{1}{1-Ke^{-t}}[/tex]

Step-by-step explanation:

Given

The given equation is a differential equation

[tex]\dfrac{dy}{dt}=y-y^2[/tex]

[tex]\dfrac{dy}{dt}=-(y^2-y)[/tex]

By separating variable

⇒[tex]\dfrac{dy}{(y^2-y)}=-t[/tex]

[tex]\left(\dfrac{1}{y-1}-\dfrac{1}{y}\right)dy=-dt[/tex]

Now by taking integration both side

[tex]\int\left(\dfrac{1}{y-1}-\dfrac{1}{y}\right)dy=-\int dt[/tex]

⇒[tex]\ln (y-1)-\ln y=-t+C[/tex]

Where C is the constant

[tex]\ln \dfrac{y-1}{y}=-t+C[/tex]

[tex]\dfrac{y-1}{y}=e^{-t+c}[/tex]

[tex]\dfrac{y-1}{y}=Ke^{-t}[/tex]

[tex]y=\dfrac{1}{1-Ke^{-t}}[/tex]

from above equation we can say that

When t  will increases in positive direction then [tex]e^{-t}[/tex] will decreases it means that [tex]{1-Ke^{-t}}[/tex] will increases, so y will decreases. Similarly in the case of negative t.

Ver imagen Netta00
ACCESS MORE